The effects of self-regulated learning strategies on academic procrastination and academic success among college EFL students in China - Tao, Xue; Hanif, Hafiz; Lieqin, Wang (Frontiers in Psychology, 2025)
The failure of self-regulation lies at the core of academic procrastination, which poses a serious threat to academic success. This study examines the direct impact of self-regulated strategies on academic procrastination and academic success among university students. Additionally, it explores the mediating role of academic procrastination in the relationship between metacognitive strategies, time management, effort regulation, and students’ academic success. A fully quantitative study was conducted among 239 university students who learn English as a foreign language. In order to examine how self-regulated learning strategies can help university EFL students overcome academic procrastination and enhance academic success, 10 hypotheses were put to the test. The hypothesized model was tested using structural equation modeling (SEM) implemented in AMOS 23.0. Bootstrapping with bias-corrected confidence intervals was employed to evaluate the model’s path coefficients and mediation effects. The results reveal that there is a significant positive correlation between metacognitive strategies and academic success. Learning strategies such as effort regulation, metacognitive strategies, and time management are negatively associated with academic procrastination, and academic procrastination is negatively related to academic success. Regarding the mediation effects, it was found that effort regulation and time management have a significantly positive indirect influence on student’s academic success through the mediation of academic procrastination. Meanwhile, academic procrastination does not mediate the relationship between metacognitive strategies and students’ academic success. This study offers significant empirical evidence underscoring the critical role of self-regulated learning in academic success, while emphasizing the necessity of implementing targeted interventions to mitigate academic procrastination as a key impediment to student success. The implications of this study can assist educators or teachers in guiding students to appropriately apply self-regulated learning strategies and models to English learning.